A Comparative Study on Assessing the Summative Assessments Before and After Implementing Competency-Based Medical Education in India - Arijit Datta; Preeti Tiwari; Dhara Goswami; Darshan Galoria; Prashant Verma (Journal of Medical Education and Curricular Development)
Introduction Competency-Based Medical Education [CBME] is a framework for organizing medical education programs that emphasize ongoing assessments to monitor learners’ progress. Implemented by the erstwhile Medical Council of India since the 2019–2020 academic year, this approach has influenced undergraduate summative assessments for Forensic Medicine. To assess the implementation, effectiveness, and alignment of the new curriculum with the goals of medical education, it is necessary to compare summative assessment question papers of undergraduate MBBS students from 2017 to 2020. Methodology Researchers evaluated 32 summative examination question papers from eight medical universities across India, categorizing them into structured, non-structured, and action verb-based categories, according to Bloom's revised taxonomy's cognitive domain (remember, understand, apply, analyze, evaluate, and create). They compared the data with the pre- and post-implementation benchmarks of the CBME curriculum of the National Medical Commission (NMC) from the 2019 batch MBBS program. Results Most universities used unstructured questions and most marks were allocated to remember the levels of the cognitive domain. It was also found that marks were skewed towards specific topics in all universities, leading to inappropriate sampling and coverage of the competencies. The study also revealed that core areas, such as medical jurisprudence and toxicology, were inappropriately assessed. Conclusion The quality of the summative exam questions in Forensic Medicine and Toxicology subjects was poor and not aligned with the CBME, highlighting the need to assess the clarity and utility of blueprints currently employed by universities.